Language in Context: Exploring Style Variation in The Class of English for Journalism - Yulianto, Andrias (Universitas Muhammadiyah Lampung, 2025)
Language styles are present in different social groups in the communication process, and this language phenomenon necessitates attention to ensure effective communication.The objective of this research is to investigate the ways in which different language styles are produced, as well as the extent to which social factors and dimensions drive the use of certain languages.This research utilizes qualitative methods, with participant observation serving as the primary data collection technique. The data are the utterances of the participants (students and lecturers) of the English for Journalism class. The findings of this study demonstrate the existence of at least four styles that are alternately employed in this class, namely formal, intimate, consultative, and casual. Various societal factors also tend to play an active role in the selection of a particular language style, namely setting, participants, situation and topic, social-solidarity distance, status, formality, and referential and affective function scale. These findings underscore the adaptability of language choice in the classroom, which is flexible and adapts to the interaction of social factors and classroom context.